Leadership in Action: Branching out: Social Identity Comes to the Forefront - Hannum, Kelly (Center for Creative Leadership, 2008)
Leaders can use an understanding of social identity to decrease their likelihood of misunderstanding others, increase their openness to different perspectives, and enhance their skill at accurately interpreting situations that call on their ability to lead.